2014
DOI: 10.1016/j.jtcvs.2013.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Sublobar resection is equivalent to lobectomy for clinical stage 1A lung cancer in solid nodules

Abstract: Sublobar resection and lobectomy have equivalent survival for patients with clinical stage IA non-small cell lung cancer in the context of computed tomography screening for lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
226
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(247 citation statements)
references
References 33 publications
12
226
0
2
Order By: Relevance
“…However, sublobar resection is another surgical option, whose features include a low complication rate, short hospitalization duration, and a high preservation of lung function (23,24). In recent studies, sublobar resection has shown equivalent oncological results and survival outcome compared with lobectomy (25)(26)(27). Moreover, in 2010, Sugi and colleagues reported a retrospective study of 159 patients, revealing that there were no significant differences among the wedge resection, segmentectomy, and lobectomy approaches in the treatment of small NSCLC (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, sublobar resection is another surgical option, whose features include a low complication rate, short hospitalization duration, and a high preservation of lung function (23,24). In recent studies, sublobar resection has shown equivalent oncological results and survival outcome compared with lobectomy (25)(26)(27). Moreover, in 2010, Sugi and colleagues reported a retrospective study of 159 patients, revealing that there were no significant differences among the wedge resection, segmentectomy, and lobectomy approaches in the treatment of small NSCLC (28).…”
Section: Discussionmentioning
confidence: 99%
“…The only case who had a one-stage bilateral lobectomy in our series suffered complications necessitating artificial ventilation for 4 days. Sublobar resection has been shown to be equivalent to lobectomy for clinical stage-IA solitary lung cancers (19). However, Zuin and colleagues (18) showed that patients who had a lobectomy showed better 5-year survival than those who underwent sublobar resection (57.5% and 36%, respectively, P=0.016).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the classification of lesions employed was not known given the different prognoses of various subtypes of lesions (4). For patients with small-sized and well-differentiated lesions, such as pGGO <2 cm and AIS/MIA, 5-year survival might not necessarily be compromised by sublobar resections (segmentectomy and wedge resection) (19,20). Thus, a one-stage bilateral procedure might be suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Several single centre retrospective studies have been published with conflicting conclusions (21,22 (24). CT imaging was used to determine the invasive potential of the tumour on the basis of the ratio of consolidation (C) to the maximal tumour diameter (T) (C/T ratio).…”
Section: Conservative Interventions: Sublobar Resection (Slr) and Bromentioning
confidence: 99%